Variability of nutrients and chlorophyll a in Ancao Inlet during a spring tidal cycle in April 2009 - Alcantara, P. (2012)
Sao Luis or Ancao Inlet is the most western of the six inlets of the Ria Formosa lagoon, in southern Portugal. This inlet contributes relatively little to the water volume exchange over a tidal cycle (similar to 10%). Temperature, salinity, pH, dissolved oxygen, and chlorophyll a and nutrient concentrations were measured hourly at the surface, at an intermediate level, and near the bottom over a complete spring tidal cycle, at a sampling point in the middle of the inlet. Current velocity was also measured hourly over the entire cross-section of the inlet using an acoustic Doppler current meter. From these parameters, the flow rate and the transport of nutrients and chlorophyll a were calculated and integrated over the complete tidal cycle providing the net transport. The results show that this is a well-mixed dynamic inlet where, during spring tide, the tidal signal is evident particularly for the nutrient and chlorophyll a concentrations. The nutrient concentrations were low (almost depleted), while the chlorophyll a concentrations were high (4-6 mg m(-3)). The estimated transports through Ancao Inlet revealed that there was a net import of chlorophyll a, nitrate, and phosphate to the Ria Formosa lagoon, while silicate was exported to the adjacent coastal area.